Hubble space telescope combined strong and weak lensing analysis of the CLASH sample: mass and magnification models and systematic uncertainties - Zitrin, Adi; Fabris, Agnese; Bartelmann, Matthias; Carrasco, Mauricio (Arxiv, 2015)
We present results from a comprehensive lensing analysis in HST data, of the complete CLASH cluster sample. We identify new multiple-images previously undiscovered allowing improved or first constraints on the cluster inner mass distributions and profiles. We combine these strong-lensing constraints with weak-lensing shape measurements within the HST FOV to jointly constrain the mass distributions. The analysis is performed in two different common parameterizations (one adopts light-traces-mass for both galaxies and dark matter while the other adopts an analytical, elliptical NFW form for the dark matter), to provide a better assessment of the underlying systematics - which is most important for deep, cluster-lensing surveys, especially when studying magnified high-redshift objects. We find that the typical (median), relative systematic differences throughout the central FOV are $\sim40%$ in the (dimensionless) mass density, $κ$, and $\sim20%$ in the magnification, $μ$. We show maps of these differences for each cluster, as well as the mass distributions, critical curves, and 2D integrated mass profiles. For the Einstein radii ($z_{s}=2$) we find that all typically agree within $10%$ between the two models, and Einstein masses agree, typically, within $\sim15%$. At larger radii, the total projected, 2D integrated mass profiles of the two models, within $r\sim2\arcmin$, differ by $\sim30%$. Stacking the surface-density profiles of the sample from the two methods together, we obtain an average slope of